Analysis of Illocutionary Speech Acts on 'Whatshapp' Social Media - Sri Rahayu; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
Whatsapp is an internet-based application that has the potential to be used as a medium of This research is motivated by the use of social media among the communitywhich is expanding. One of the most popular messaging media today is WhatsApp. The author analyzes illocutionary speech acts in private WhatsApp conversations. The formulation of the problem in this research is (1) What are the forms of illocutionary speech acts that exist in Private WhatsApp conversations. (2) What is the meaning of the illocutionary speech acts found in conversations on the WhatsApp application? This study follows a pragmatic approach, the object of research is Sri Rahayu's personal WhatsApp conversations with 15 screenshots and 134 utterances. Special pragmatics in the study of speech in the form of illocutionary proposed by Searle (1969) classifies speech acts into five types, namely (1) representative speech acts, (2) directive, (3) expressive, (4) commissive, and (5) declarative . Based on the results of data analysis, it can be concluded that the form of WhasApp speech consists of: (1) The existing forms of illocutionary speech acts, namely 6 utterances of assertive speech acts, 16 directive speech acts, 4 commissive speech acts, 7 expressive speech acts utterances, and declarative speech acts as many as 2 utterances. (2) The meaning of Illocutionary Acts, which means complaining, asking, asking, proposing, warning, inviting, offering, canceling, surrendering and expressing willingness.